2015 IEEE Sensors Applications Symposium (SAS) 2015
DOI: 10.1109/sas.2015.7133628
|View full text |Cite
|
Sign up to set email alerts
|

Design of sensor node for air quality crowdsensing

Abstract: Information on air-quality in urban environments is typically measured only at limited number of sites, due to cost of measurement of atmospheric concentrations of toxic gases (CO, NO2, SO2) within accuracy boundaries defined by regulative bodies. Low spatial resolution of the mentioned environmental parameters hinders their applications in localization of the air-pollution sources, traffic regulation or studies of chronic respiratory diseases related to personal pollution exposure. Thus, we propose complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Calibration: Accuracy of low-cost sensors can be improved through calibration, both in the laboratory before deployment, and also at regular intervals while in the field. Laboratory calibration has shown that low-cost air quality sensors have high potential [20], [21], but the process is costly and timeconsuming. Low-cost sensors also suffer from cross-sensitivity to other pollutants in-field, and changing environmental conditions such as strong winds, high temperature, and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration: Accuracy of low-cost sensors can be improved through calibration, both in the laboratory before deployment, and also at regular intervals while in the field. Laboratory calibration has shown that low-cost air quality sensors have high potential [20], [21], but the process is costly and timeconsuming. Low-cost sensors also suffer from cross-sensitivity to other pollutants in-field, and changing environmental conditions such as strong winds, high temperature, and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Crowd sensing is one of the major methodology in the ambient air screening, a sensor node by using this technique is presented by Oletic et al in [9]. In this approach, the individuals are able to participate in the experiment by the infrastructure of a network of mobile sensors, to measure the factors.…”
Section: Related Workmentioning
confidence: 99%
“…Wireless sensor network (WSN) has been used along with Raspberry Pi, Arduino, and Zigbee to monitor the environment [13] using low cost sensors [14]. Two gas sensors, temperature, humidity, and atmospheric pressure sensors, were utilized in [15]. Smartphone with additional device was used to form crowd-sensing [16][17][18].…”
Section: Introductionmentioning
confidence: 99%